2019
DOI: 10.1111/hequ.12237
|View full text |Cite
|
Sign up to set email alerts
|

Cultures of sustainability governance in higher education institutions: A multi‐case study of dimensions and implications

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 33 publications
(80 reference statements)
2
51
0
2
Order By: Relevance
“…Such questioning should be done within the institutions by reflecting on the values that are deterring academics from redesigning their disciplines and appreciating the epistemology and multicultural vision of sustainability [7]. In this regard, being aware of the institution's cultural predispositions and willingness to transform is critical for enhancing HEIs sustainability governance [30]. These studies already point to the crucial action of the human factor and the underlying worldviews and value systems within HEIs as barriers to change in some cases, or drivers of change in others [7,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such questioning should be done within the institutions by reflecting on the values that are deterring academics from redesigning their disciplines and appreciating the epistemology and multicultural vision of sustainability [7]. In this regard, being aware of the institution's cultural predispositions and willingness to transform is critical for enhancing HEIs sustainability governance [30]. These studies already point to the crucial action of the human factor and the underlying worldviews and value systems within HEIs as barriers to change in some cases, or drivers of change in others [7,30].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, being aware of the institution's cultural predispositions and willingness to transform is critical for enhancing HEIs sustainability governance [30]. These studies already point to the crucial action of the human factor and the underlying worldviews and value systems within HEIs as barriers to change in some cases, or drivers of change in others [7,30]. Further research is needed to better understand the relation between HEIs institutional cultures and sustainability transformations.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the results of the study, it may also be useful to include aspects of organizational culture in the consideration. As Niedlich et al [32] have shown in their study, organizational culture plays a crucial role in HEI's governance for the implementation of sustainability aspects. Cultural orientations at management level can thus act as a stimulus or barrier to the success or failure of implementation.…”
Section: Discussionmentioning
confidence: 84%
“…According to Niedlich et al [72] (p. 3), a HEI needs to change its institutional culture if SD shall be put in practice because SD affects the whole HEI as an organization. They identified four categories of organizational culture as key areas for SD governance at a HEI.…”
mentioning
confidence: 99%
“…They identified four categories of organizational culture as key areas for SD governance at a HEI. We emphasize the fourth, highlighting the importance of a "holistic governance covering all core areas of higher education institutions-teaching, research, operations and outreach" [72] (p. 4). With our findings, we are able to support this argument since it is crucially important for a HEI that the goal to realize SD at the whole university level is commonly pursued bottom-up and top-down.…”
mentioning
confidence: 99%